Whistleblowing : de outros ordenamentos jurídicos à Lei nº 13.608/2018 e suas modificações - Arguello, Mariana Elgers (2022)
Typical of common law legal systems, the whistleblowing institute entered the Roman- Germanic legal systems, including in Brazil, with poor regulation. American legislation, through numerous cases, forced itself to build consistent regulations in order to guarantee whistleblower protections and avoid economic crises, as occurred during the Enron case. The European Union, in order to prevent any crises, imposed a unique legislation, given that some countries still, in the middle of 2019, did not have any regulations on the practice of whistleblowing. Brazil, inspired by the American legislation, tried to carry out the transplant of the United States institute, however, the failure was already announced. Law nº 13.608/2018, modified by the Pacote Anticrime, is immature and incomplete since its inception, demonstrating the need for a vast complement in all aspects that safeguard the practice of whistleblowing. The analysis, carried out on each article, in line with the bills brought to the fore, demonstrate how flawed Brazilian legislation is. The suggestion adopted by this research follows in the direction of improving what is currently in force, however, one must, firstly, analyze the constitutionality of the legislation under penalty of violating fundamental rights.